2006
DOI: 10.1093/bioinformatics/btl281
|View full text |Cite
|
Sign up to set email alerts
|

Combination of text-mining algorithms increases the performance

Abstract: The LDD corpus presented is available by request to the author. The system will be available shortly. For information and updates on CONAN please visit http://www.cs.uu.nl/people/rainer/conan.html.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…Evaluation of the accuracy of integrated data is a necessary step and generally is expressed in terms of precision (the ability to identify the correct entities in the abstracts relative to the number of all identified entities of the same type), recall (the ability to identify correct entities of specific type present in the abstracts relative to all such entities present in the abstracts) and F-measure [41]. Since it is not possible to evaluate every concept from each of the dictionaries across all 5,243 documents, we selected the SCN1A gene as the reference.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of the accuracy of integrated data is a necessary step and generally is expressed in terms of precision (the ability to identify the correct entities in the abstracts relative to the number of all identified entities of the same type), recall (the ability to identify correct entities of specific type present in the abstracts relative to all such entities present in the abstracts) and F-measure [41]. Since it is not possible to evaluate every concept from each of the dictionaries across all 5,243 documents, we selected the SCN1A gene as the reference.…”
Section: Discussionmentioning
confidence: 99%
“…As the combination of relation extraction methods has previously been shown to increase overall system performance [23,27], we decided to combine both co-occurrence and NLP methods to enhance the overall performance. For the text retrieval, we apply co-occurrence to obtain high sensitivity, while in the relation extraction phase, we apply NLP and rule-based methods to gain high specificity.…”
Section: Methodsmentioning
confidence: 99%
“…Text-mining is a simple process of extracting knowledge from text. In this research, we need text-mining algorithms as part of our suggested solution at the level of user interest classification [19,20]. This classification is based on the text in the tweets of users.…”
Section: Classification Of Twitter Usersmentioning
confidence: 99%